Potent and Selective Inhibitors of Trypanosoma cruzi Triosephosphate Isomerase with Concomitant Inhibition of Cruzipain: Inhibition of Parasite Growth through Multitarget Activity. (23rd October 2015) - Aguilera, Elena; Varela, Javier; Birriel, Estefanía; Serna, Elva; Torres, Susana; Yaluff, Gloria; de Bilbao, Ninfa Vera; Aguirre‐López, Beatriz; Cabrera, Nallely; Díaz Mazariegos, Selma; de Gómez‐Puyou, Marieta Tuena; Gómez‐Puyou, Armando; et al.
Abstract: Triosephosphate isomerase (TIM) is an essential Trypanosoma cruzi enzyme and one of the few validated drug targets for Chagas disease. The known inhibitors of this enzyme behave poorly or have low activity in the parasite. In this work, we used symmetrical diarylideneketones derived from structures with trypanosomicidal activity. We obtained an enzymatic inhibitor with an IC50 value of 86 nm without inhibition effects on the mammalian enzyme. These molecules also affected cruzipain, another essential proteolytic enzyme of the parasite. This dual activity is important to avoid resistance problems. The compounds were studied in vitro against the epimastigote form of the parasite, and nonspecific toxicity to mammalian cells was also evaluated. As a proof of concept, three of the best derivatives were also assayed in vivo. Some of these derivatives showed higher in vitro trypanosomicidal activity than the reference drugs and were effective in protecting infected mice. In addition, these molecules could be obtained by a simple and economic green synthetic route, which is an important feature in the research and development of future drugs for neglected diseases. Abstract : Two birds. One stone . Multitarget agents were developed that act against triosephosphate isomerase (TIM) and cruzipain, two key enzymes in Trypanosoma cruzi, the causative agent of Chagas disease. The compounds exhibited nanomolar range inhibition of Tc TIM and protection profiles in vivo, with the best compound exhibiting an IC50 value of 86 nm against Tc TIM in an enzymatic assay, and an IC50 value of 600 nm against the epimastigote form of T. cruzi, Tulahuen 2 strain.